Microfluidic Electrospray Niacin Metal-Organic Frameworks Encapsulated Microcapsules for Wound Healing - Guopu Chen; Yunru Yu; Xiuwen Wu; Gefei Wang; Guosheng Gu; Feng Wang; Jianan Ren; Huidan Zhang; Yuanjin Zhao (Research, 2019)
Niacin metal-organic frameworks (MOFs) encapsulated microcapsules with alginate shells and copper-/zinc-niacin framework cores were in situ synthesized by using a microfluidic electrospray approach for wound healing. As the alginate shells were bacteria-responsively degradable, the niacin MOFs encapsulated microcapsules could intelligently, controllably, and programmably release calcium, copper, and zinc ions, depending on the degree of infections. The released ions could not only kill microbes by destroying their membrane and inducing the outflow of nutrient substance, but also activate copper/zinc superoxide dismutase (Cu/Zn-SOD) to eliminate oxygen free radicals and rescue the cells from oxidative stress injury. Furthermore, the simultaneously released niacin could promote hemangiectasis and absorption of functional metal ions. Thus, the niacin MOFs encapsulated microcapsules were imparted with outstanding antibacterial, antioxidant, and angiogenesis properties. Based on an in vivo study, we have also demonstrated that the chronic wound healing process of an infected full-thickness skin defect model could be significantly enhanced by using the niacin MOFs encapsulated microcapsules as therapeutic agent. Therefore, the microfluidic electrospray niacin MOFs encapsulated microcapsules are potential for clinical applications.